Characterizing fluoroscopy based kinematic accuracy as a function of pulse width and velocity. Issue 15 (7th November 2016) - Ellingson, Arin M.; Mozingo, Joseph D.; Magnuson, Dixon J.; Pagnano, Mark W.; Zhao, Kristin D.
Abstract: Fluoroscopic imaging has become increasingly popular to investigate total knee arthroplasty kinematics non-invasively − 3D implant models are aligned with 2D image projections, and optimized via an edge-contour alignment technique. Previous studies have quantified the accuracy of this approach, however they do not always adequately address the impact of image collection parameters. A particularly sensitive parameter is the pulse width, or exposure time per frame. At longer pulse widths, more motion is captured in a single frame; this can lead to image blur and subsequent degradation to image edge quality. Therefore, the comparative accuracy of relative joint kinematics as a function of pulse width and joint velocity needs to be defined. A limits of agreement approach was taken to define the mean differences between optoelectric kinematic measures (gold standard) and fluoroscopic methods at various pulse widths (1, 8 and 16 ms) and knee velocities (50, 100 and 225°/s). The mean absolute differences between the optoelectric and fluoroscopic methods for 1 ms pulse width were less than 1.5° and 0.9 mm. Comparable rotational differences (1.3°) were observed for the 8 ms pulse width but had larger translational differences (1.4 mm). The 16 ms pulse width yielded the greatest mean differences (2.0° and 1.6 mm), which increased with knee flexion velocity. The importance of pulse width and velocity should not be overlooked for future studies – this parameter has proven to be a sensitive metric in the quantification of joint motion via fluoroscopy and must be identified and reported in future studies.